Electronic-oscillator analysis of femtosecond four-wave mixing in conjugated polyenes - Meier, Torsten; Tretiak, S.; Chernyak, V.; Mukamel, S. (Physical Review B)
Equations of motion which describe the nonlinear optical response of conjugated polyenes using a collective electronic-oscillator representation are derived. Specific signatures of electronic correlations which enter as anharmonicities and scattering between oscillators are predicted in ultrafast resonant four-wave mixing. Only few resonant oscillators need to be considered explicitly; effects of the remaining (off-resonant) oscillators are introduced via renormalized anharmonic coupling coefficients. The connection with inorganic semiconductors is established.

Conservation of intraband coherence upon carrier relaxation by LO-phonon emission - Meier, Torsten; Wolter, F.; Roskos, H.G.; Je, K.-C; Hader, J.; Rossi, F.; Köhler, K.; Koch, S.W.; Kurz, H. (Quantum Electronics and Laser Science Conference)
The evolution of the quantum mechanical phase of electronic wave packets on seattering-with phonons is an issue of great relevance in solid-state physics. In semiconductor superlattices, evidence for phase conservation on scattering was obtained when time-resolved THz-emission experiments indicated that the dephasing of the probed intraband coherence may proceed slower than the relaxation of carriers via emission of LO-phonons estimated to occur on a 200-fs time scale as in bulk GaAs.1 To corroborate this interpretation, the unknown LO-phonon emission times in the superlattices must be measured for the experimental conditions of the THz-emission experiments. In this paper, a combined investigation of the coherent and incoherent dynamics of optically excited charge carriers in a superlattice structure is presented. A comparison of the characteristic time constants provides clear evidence for the conservation of the phase of the intraband coherence on LO-phonon relaxation.

Nonlinear dynamics of the coupled exciton-cavity system - Meier, Torsten; Koch, M.; Shah, J. (Quantum Electronics and Laser Science Conference)
In recent years the linear emission dynamics of microcavities containing an optical absorber has been a subject of intense research. For strong coupling between the cavity and the absorber, the spectrum of the coupled system shows two peaks and the linear dynamics of the coupled system is dominated by pronounced oscillations at the normal mode frequency.1 Yet, the uniqueness of the coupled absorber-cavity system cannot be concluded from its linear dynamics.

Multiple Exciton Coherence Sizes in Photosynthetic Antenna Complexes viewed by Pump-Probe Spectroscopy - Meier, Torsten; Chernyak, V.; Mukamel, S. (The Journal of Physical Chemistry B)
The pump−probe signal from the light-harvesting antenna LH2 of purple bacteria is analyzed using a Green function expression derived by solving the nonlinear exciton-oscillator equations of motion (NEE). A microscopic definition of the exciton mean free path (Lf) and localization size (Lρ) is given in terms of the off-diagonal elements of the exciton Green function and density matrix, respectively. Using phonon-induced (homogeneous) and disorder-induced (inhomogeneous) line widths compatible with superradiane measurements, we find that at 4.2 K the localization size is Lρ = 15 and that the shift ΔΩ between the positive and negative peaks in the differential absorption is determined by a different effective size Lf/2 = 5.6 associated with the exciton mean free path. Our model further predicts the recently observed superradiance coherence size determined by Lρ.

Wohnzimmer und Satelliten. Die Empirie der Fernsehwissenschaften - Adelmann, Ralf; Stauff, Markus (montage/av. Zeitschrift für Theorie und Geschichte audiovisueller Kommunikation)

Bericht aus der Arbeitsgruppe Erziehungswissenschaft - Herzig, Bardo (Neue Medien – neue Aufgaben für die Lehrerausbildung)

Praxis- und theorieorientierte Entwicklung und Evaluation von Konzepten für pädagogisches Handeln - Tulodziecki, G.; Herzig, Bardo

Der Kinderfilm im Multimedia-Zeitalter - Herzig, Bardo (Perfo 1/1997)

Dynamic data structures for realtime management of large geometric scenes - Fischer, Matthias; Meyer auf der Heide, Friedhelm; Strothmann, Willy-Bernhard (5th Annual European Symposium on Algorithms (ESA '97))
We present a data structure problem which describes the requirements of a simple variant of fully dynamic walk-through animation: We assume the scene to consist of unit size balls in R2 or higher dimensions. The scene may be arbitrarily large and has to be stored in secondary memory (discs) with relatively slow access. We allow a visitor to walk in the scene, and a modeler to update the scene by insertions and deletions of balls. We focus on the realtime requirement of animation systems: For some t (specified by the computation power of (the rendering hardware of) the graphic workstation) the data structure has to guarantee that the balls within distance t of the current visitor's position are presented to the rendering hardware, 20 times per second. Insertions and deletions should also be available to the visitor with small delay, independent of the size of the scene. We present a data structure that fulfills the above task in realtime. Its runtime is output-sensitive, i.e. linear in a quantity close to the output size of the query. We further present (preliminary) experimental results indicating that our structure is efficient in practice.

Carlstedt, Mikko (Mikko [Mikael] Vilhelm Sakari) - Heinrichs, Ulrike (Allgemeines Künstlerlexikon)

Capsia (Capsius), Margareta (verh. Gavelin) - Heinrichs, Ulrike (Allgemeines Künstlerlexikon)

Carlstedt, Kalle (Kaarlo Fredrik Oskar) - Heinrichs, Ulrike (Allgemeines Künstlerlexikon)

(4×2) and (2×4) reconstructions of GaAs and InP(001) surfaces - Schmidt, Wolf Gero (Applied Physics A: Materials Science & Processing)

The anisotropic electron - positron momentum distribution in diamond - Nilen, R W N; Connell, S H; Britton, D T; Fischer, C G; Sendezera, E J; Schaaff, P; Schmidt, Wolf Gero; Sellschop, J P F; Verwoerd, W S (Journal of Physics: Condensed Matter)

Electron-positron momentum density distribution in diamond - Nilen, R.W.N.; Connell, S.H.; Schmidt, Wolf Gero; Britton, D.T.; Verwoerd, W.S.; Sellschop, J.P.F.; Shrivastava, S. (Applied Surface Science)

Antimony-stabilized GaAs(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Chemisorption of arsenic on InP(110) - Großner, U.; Schmidt, Wolf Gero; Bechstedt, F.; Santos, P.V.; Koopmans, B.; Esser, N. (Surface Science)

Comparison of As-rich and Sb-terminated GaAs(100)(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

A High Resolution Investigation of the Anisotropic Electron-Positron Momentum Distribution in Diamond - Nilen, R.W.N.; Connell, S.H.; Britton, D.T.; Fischer, C.G.; Sendezera, E.J.; Schmidt, Wolf Gero; Sellschop, J.P.F.; Verwoerd, W.S. (Materials Science Forum)

As on InP(110) studied within density-functional theory - Grossner, U.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)